Theoretical study on the photoelectric response properties of trilayer PtSe2/SnSeS/PtSe2 and SnSeS/PtSe2/SnSeS for digital media technology - Zhou, Zhaopeng; Jiang, Anqi (Elsevier B.V., 2026)
Heterostructure-based photodetectors have garnered significant research attention owing to their superior electrical and photoresponsive properties. In the present study, the optoelectronic characteristics of trilayer PtSe2/SnSeS/PtSe2 and SnSeS/PtSe2/SnSeS heterojunctions were systematically examined through first-principles calculations. The findings reveal that both trilayer heterojunctions exhibit indirect band gaps of 0.278 eV and 0.301 eV, respectively, along with type-II band alignment. Interfacial charge transfer within these trilayer heterojunctions induces a pronounced built-in electric field. Furthermore, the band gap values of the PtSe2/SnSeS/PtSe2 and SnSeS/PtSe2/SnSeS heterojunctions can be modulated by biaxial strain, variations in interlayer spacing, and the application of external electric fields. The absorption coefficient peaks for the trilayer heterojunctions attain magnitudes of 1.81 × 105 cm−1 and 1.83 × 105 cm−1, respectively. These results underscore the promising potential of trilayer PtSe2/SnSeS/PtSe2 and SnSeS/PtSe2/SnSeS heterostructures for deployment in advanced optoelectronic devices with enhanced performance.